2015
DOI: 10.1523/jneurosci.2891-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory Recruitment of Bilateral Visual Cortex during Spatial Attention to Competing Rhythmic Inputs

Abstract: Selective attention uses temporal regularity of relevant inputs to bias the phase of ongoing population-level neuronal oscillations. This phase entrainment streamlines processing, allowing attended information to arrive at moments of high neural excitability. How entrainment resolves competition between spatially segregated inputs during visuospatial tasks is not yet established. Using high-density electroencephalography in humans, a bilateral entrainment response to the rhythm (1.3 or 1.5 Hz) of an attended s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 60 publications
4
44
0
Order By: Relevance
“…We found a similar negative relationship between alpha and reporting of touch over ipsilateral somatosensory cortex on touch absent trials as we found over contralateral cortex. Alpha over sensory regions other than the primary region associated with a task may play a key role in suppressing irrelevant information -the gating-by-inhibition hypothesis -as seen in a number of studies of spatial attention (Gray, Frey, Wilson, & Foxe, 2015;Haegens et al, 2011Haegens et al, , 2011Jensen & Mazaheri, 2010). Thus, when attending to the right hand, alpha power increases over right, ipsilateral somatosensory cortices and decreases over left, contralateral somatosensory cortices.…”
Section: Discussionmentioning
confidence: 98%
“…We found a similar negative relationship between alpha and reporting of touch over ipsilateral somatosensory cortex on touch absent trials as we found over contralateral cortex. Alpha over sensory regions other than the primary region associated with a task may play a key role in suppressing irrelevant information -the gating-by-inhibition hypothesis -as seen in a number of studies of spatial attention (Gray, Frey, Wilson, & Foxe, 2015;Haegens et al, 2011Haegens et al, , 2011Jensen & Mazaheri, 2010). Thus, when attending to the right hand, alpha power increases over right, ipsilateral somatosensory cortices and decreases over left, contralateral somatosensory cortices.…”
Section: Discussionmentioning
confidence: 98%
“…15,16 Finally, the Spatial CTET is known to produce reliable deployment of alpha activity. 14 It is, therefore, particularly well suited to the current investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The primary task employed in the present experiment was the Spatial Continuous Temporal Expectancy Task (Spatial CTET 14 ). As a variant of a Continuous Performance Task (CPT), the Spatial CTET requires sustained visuospatial attention to a stream of visual information over a time-scale of several minutes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations